The effects of a higher amount of iodine supplement on the efficiency of laying hens fed extruded rapeseed and on eggshell quality - M. Lichovniková; L. Zeman (Czech Journal of Animal Science, 2004)
The objective of this experiment was to study the effects of feeding 6.07 mg/kg of iodine in comparison with 3.57 mg/kg of iodine as a supplement in diets with different levels of extruded rapeseed (4.5, 9.0 and 13.5%) for a period of 52 weeks. The higher amount of iodine had the most marked effect on the egg mass production and on the feed : egg mass ratio when the hens were fed 9.0% extruded rapeseed in the diet. The egg mass production increased from 55.5 ± 1.06 g/d to 57.8 ± 1.12 g/d and the feed : egg mass ratio was improved from 2.15 kg/kg to 2.02 kg/kg. The eggshell weight ratio significantly (P < 0.05) increased in all groups with the higher level of iodine. The higher level of iodine significantly (P < 0.05) increased eggshell thickness in the groups with 9.0 and 13.5% of extruded rapeseed and it also significantly (P < 0.01) increased eggshell strength in the groups with 4.5 and 9.0% of rapeseed in the diets.